Effect of the particle size range of construction and demolition waste on the fresh and hardened-state properties of fly ash-based geopolymer mortars with total replacement of sand - De Rossi, A. (2019)
This study seeks the valorization of industrial residues (fly ash and construction and demolition waste (CDW)) through the production of geopolymer mortars. The effect of the sand substitution by CDW and the influence of the particle size range of CDW fine aggregates on the fresh and hardened properties of the mortars were evaluated. Geopolymer mortars were produced using biomass fly ash waste and metakaolin as a binder, CDW as fine aggregates, and an alkali solution of sodium silicate and sodium hydroxide as activator. The geopolymer mortars were characterized in fresh state by the flow table test and in the hardened state through chemical, physical/microstructural analyzes. The mortars produced with CDW showed lower flowability when compared to the ones prepared with sand. The compressive and flexural strength of hardened mortars, respectively, obtained with residues were higher when compared to sand: 40 MPa and 8.5 MPa with CDW, against 23 MPa and 3.1 MPa for sand-based samples. It was observed that mortars developed with recycled aggregate and natural aggregate present similar chemical and mineralogical compositions. The superior results obtained in the mechanical properties of mortars produced with CDW are related to the recycled aggregate-geopolymer paste interface.